(3GdfXQjI GdGbJUGOjI GdcdjIs - (3fYeI Gddg(B, (3GMeO QeVGfs; (3GjeGf YWjI fGUas ((3GdGScfOQjIc GdOGQ GdLGeYjIs, 2003)
(3jJfGhd gPG GdcJGH OQGSI Sdhc GdGbJUGO ccd ef MjK GdQhGL hGdcSGO hGdfGJL Gdcdi ef GdSdY GdeSJNdU GdJTGHc Hjf GdbWGYGJ GdGbJUGOjI , OGdI GdGSJgdGc, GdGSJKeGQ, GdWdH GdMchej , GdJhGRf aj Shb GdGfJGL, GdYQV GdfbOj , GdWdH Ydi GdfbhqO, GdJhGRf aj GdShb GdfbOj , JMOjO GdJhGRf aj Shb GdGfJGL h GdShb GdfbOj, JhGRf GdONd Gdbhej aj Xd GdGbJUGO GdeaJhM , GdJVNe hGdfXQjGJ GdeaSQI dg GdGWGQ GdJMdjdj ddJVNe, JMdjd CKQ GdUOeI GdYQV hUOeGJ GdWdH GdJVNejI , eaghe GdJNda h NUGFUgeaghe Gdfeh hGdJfejIs
Keywords: (3GdEbJUGO Gdcdjs; (3GdJVNes; (3GdWdHs